A novel adjunctive cleansing method to reduce colony-forming units on duodenoscopes - Kwok, Karl; Chang, Joseph; Lo, Simon; Giap, Andrew; Lim, Brian; Wu, Bechien (Endoscopy International Open, 2016)
Background and study aims: Endoscopic retrograde cholangiopancreatography-related infections are of increasing global concern due to the emergence of multidrug-resistant bacteria such as carbapenem-resistant enterobacteriaceae (CRE), with bacterial biofilm production postulated as one cause of persistent infection from such virulent organisms. Because N-acetylcysteine (NAC) has been shown to possess antibacterial and biofilm-disruption properties, we aimed to evaluate if NAC would demonstrate clinical utility in reducing the colony forming units (CFU) at the elevator end of a duodenoscope, one of the hardest areas to clean. Patients and methods: This was a pilot study of 16 procedures involving the use of a duodenoscope. After use, the elevator tip of a duodenoscope was cultured and submerged for 30 minutes, either in 20 % NAC (200 mg/mL, intervention) or in sterile water (control). After 30 minutes, the elevator tip was re-cultured.Results: Submersion of the distal end of a duodenoscope in 20 % NAC (200 mg/mL) for 30 minutes resulted in a statistically significant reduction in bacterial colony forming units compared to control (average reduction 41.6 % vs 8.8 %, P = 0.001). There was no visible damage and no optical distortion to the duodenoscope after submersion in NAC. Conclusions: In summary, NAC may be a safe, simple, and useful adjunct to currently available methods of duodenoscope reprocessing. Further research may better define NAC’s role in duodenoscope reprocessing, either broadly or specifically after procedures suspected to produce a high risk of bacterial contamination (e. g. choledocholithiasis).